OBSERVASI GAYA MENGAJAR PADA PEMBELAJARAN PENDIDIKAN JASMANI OLARAGA DAN KESEHATAN DI SMP NEGERI 1 SEDAYU - Naufal Atha Raif; Ginanjar Nugraheningsih; Dody Tri Iwandana (Dharmas Journal of Sport, 2023)
This observation aims to determine the style of teaching sports and health physical education at SMP N 1 Sedayu. This type of observation is a type of quantitative descriptive observation. The subject of this research is a sports teacher at SMP N 1 Sedayu. Data collection techniques were carried out by interviews, observation, and documentation. The results showed that the teaching style used by the sports teacher at SMP N 1 Sedayu was a command and reciprocal teaching style. In conclusion, from these observations it shows that in the teaching and learning process the sports teacher at SMP N 1 Sedayu uses a command and reciprocal teaching style.